Analisis Pembelajaran Pendidikan Agama Islam Sekolah Dasar Luar Biasa di Samarinda - Siti Nasiah (IAIN PAREPARE, 2020)
This research aims to determine the implementation of Islamic religious education learning in children with special needs in special schools in Samarinda which includes how the application of the existing curriculum in schools and how teachers apply methods that are in accordance with the needs of students and who have various disorders. Student abnormalities in the study include blind, deaf, mentally retarded, blind, disabled, autistic, and students who have learning difficulties.The type of research developed in this study is a qualitative study of primary data sources for school principals and teachers who teach Islamic religious learning in exceptional elementary schools in Samarinda. While secondary data sources include documents related to school data, Islamic religious education learning tools, student learning outcomes assessment records. Data collection uses observation, interviews, and documentation. Data analysis uses data presentation, data reduction, and conclusions.The results were obtained that the learning of Islamic religion in children with special needs in samarinda already uses curriculum 13. All SDLB schools in samarinda have no special teachers who teach Islamic religious education. The teacher makes lesson plans with curriculum curriculum adjusted material13, but the reality in the field teachers must still be able to adjust to the conditions of students, because of the limitations of diverse students so the teacher must also be able to adapt learning materials to the conditions of each child. Teacher teaching methods that are often used include lecture methods, question and answer methods and demonstration methods. The teacher uses instructional media in explaining the material.